NEUROLOGICAL COMPLICATION OF JUVENIL (IDEOPATIC) ARTRITIS IN CHILDREN 4-18 YEARS OLD (International journal of medical sciences, 2026)
Juvenile (idiopathic) arthritis (JIA) is one of the most common inflammatory connective tissue diseases in children. It is a chronic joint disorder that can have a wide variety of clinical manifestations and progressions. The main symptoms of JIA include pain, swelling, limited joint movement, and general symptoms of inflammation such as fever and fatigue. However, in addition to these disorders, children with JIA often develop neurological complications, which can significantly impair quality of life and complicate treatment. These complications remain understudied, despite their importance in clinical practice. This article discusses the main neurological complications of JIA in children aged 4-18 years.